Inhibitory effect of rapamycin on proliferation of human umbilical arterial smooth muscle cells. (4th July 2019) - Jin, Rui; Sun, Wei; Bai, Yan; Huang, Li-Jun; Qu, Fu-Jun
Abstract: Objective: Rapamycin has a protective cardiovascular effect and inhibits proliferation and migration of vascular smooth muscle cells. We investigated the effects of rapamycin on proliferation of cultured human umbilical arterial smooth muscle cells (HUASMCs) by determining interleukin-6 (IL-6) levels. Materials and methods: Adherent third-generation primary-cultured HUASMCs were used in the study, and MTT assay was used to measure the effects of different rapamycin concentrations on cell proliferation at various time points (3–96 h). RT-PCR was used to measure IL-6 mRNA expression and ELISA was used to measure IL-6 protein expression. Results: After three passages, HUASMCs displayed >90% confluence. Inhibition of cell proliferation by rapamycin was both time and dose dependent. When the action concentration of rapamycin was 100 ng·mL –1, the inhibitory effect was strongest after 48 h (30.25 ± 2.40)%, and the follow-up study was conducted after 48 h. When the action time of rapamycin was 48 h, the inhibitory effect of 150 ng·mL –1 at the action concentration was the strongest, and the inhibitory rate was (42.88 ± 3.84)%. There was no significant difference between the inhibitory effect and the action concentration of 100 ng·mL –1 ( p >.05). Moreover, low (2 ng·mL –1 ), moderate (10 ng·mL –1 ), and high (100 ng·mL –1 ) rapamycin concentrations down-regulated both IL-6 mRNA and expression factor in a dose-dependent manner. Discussion and conclusions: Rapamycin inhibits proliferation of HUASMCs in vitro and through down-regulation of IL-6 expression.